PENGARUH BRAND IMAGE, KUALITAS PRODUK, DAN REFERENCE GROUP TERHADAP MINAT BELI PRODUK KOSMETIK LIPSTIK WARDAH DI KOTA MALANG - Mardhatilah Shanti; Dimas Hendrawan (Jurnal Ilmiah Mahasiswa FEB, 2014)
Industrial cosmetics growth  has increased every  year. Cosmetic’s company try to be able to dominate the market share.  Wardah is one of cosmetics brand which is dominate the national cosmetics market in recent years. Some of Wardah’s product was received awards, and Wardah’s lipstick is one of  the  Wardah’s  product  which  was received award  since 2012. Lipstick is one of the major beauty needed for every woman.  Women want a product which based on  their needs, wants and feel comfortable to use it before  they choosed. Wardah can comunicate the value of  their  lipstick well, so it could created  the impression of quality and a positive image of it. The quality and image of product became the first criteria to generate an interest. Reference group  was  the important thing and influential in consumer behaviour, particularly in a frienship zone. In addition,  the higher education level was the higher individual concern for personal appearance too. Malang as the city of education have a behaviour and look like an educated population.  This study aims to determine the influence of brand image, product quality, and reference group to Wardah’s lipstick’s purchase intention in Malang. This study was explanatory with a quantitative approach and survey methode conducted on 150 women in Malang. Nonporbability sampling with purposive sampling technique was used. Data analysis process used by multiple linear regression analysis. Based on the hypothesis testing of F, all independent variables has simultaneously significant effect on purchase intention. t  test results also showed that brand image, product quality, and reference group particaly significant effect on purchase intention. The most dominant variable affecting purchase intention is brand image variable.Key word : Brand Image, Quality Product, Reference Group, Purcahse Intention